Pengaruh Budaya Organisasi dan Good Corporate Governance terhadap Kinerja Karyawan di RSUD K.H. Daud Arif Kuala Tungkal Jambi - Azizah Azizah; Muhammad Emil (Universitas Batanghari Jambi, 2020)
specific and detailed objectives of this study are another way to analyze the partial and simultaneous influence of organizational culture and Good Corporate Governance on employee performance at K.H. Daud Arif Kuala Tungkal Jambi Hospital. The method used is quantitative research with the design of the research used is survey research for descriptive and expansive purposes. The population of 342 employees and the technique of withdrawal of samples on a non probability. The sample in this study was taken 10% of the population, resulting in a sample of 34 employees. The data analysis technique used in this study is multiple linear regression analysis. The results showed that 1) partially obtained calculations and discussions that the cultural variables of the organization (X1) had a significant positive effect on employee performance (Y) where the calculation results showed a t count of 3,349 > t table of 1,697 to H0 rejected and H1 accepted and for good corporate governance variables (X2) shows there is a significant influence on employee performance (Y), obtained calculation t count of 2,067 > t table 1,697 so that H0 is rejected and H1 is accepted , and 2) simultaneously organizational culture (X1) and good corporate governance (X2), a significant impact on employee performance (Y), obtained a calculation of F count of 7,643 > F table 3.30 so that H0 is rejected and H1 is accepted.